The Role of Knowledge Utilization in Improving Operational Efficiency Through Organizational Learning at PT. Rudy Soetadi - Prasetio, Panji; Esthi, Raniasari Bimanti (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine the role of knowledge utilization in enhancing operational efficiency through organizational learning at PT. Rudy Soetadi. In an increasingly competitive business environment, effective knowledge management and organizational learning are critical to maintaining performance and adaptability. Using a quantitative approach, data were collected through questionnaires distributed to 109 employees and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results indicate that knowledge utilization has a significant positive effect on operational efficiency (path coefficient = 0.418, p < 0.000) and organizational learning (path coefficient = 0.865, p < 0.000). Furthermore, organizational learning also positively affects operational efficiency (path coefficient = 0.500, p < 0.000) and mediates the relationship between knowledge utilization and operational efficiency (indirect effect = 0.432, p < 0.000). The model explains 78.6% of the variance in operational efficiency (R² = 0.786). This study provides practical insights for companies seeking to leverage their knowledge assets and foster a learning culture, thereby enhancing productivity and competitive advantage.